2010
DOI: 10.1007/s00335-010-9254-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait locus analysis of ovarian cysts derived from rete ovarii in MRL/MpJ mice

Abstract: MRL/MpJ (MRL) is a model mouse for autoimmune diseases that shows dermatitis, vasculitis, arthritis, and glomerulonephritis. In addition to these immune-associated disorders, we found that aged MRL mice develop ovarian cysts originating from the rete ovarii, which is lined by ciliated or nonciliated epithelium and considered remnants of mesonephric tubules. Ovarian cysts, which are reported to have several sources, are associated with female infertility, but information regarding the genetic etiology of ovaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…In contrast, the rete ovarian cysts of MRL mice showed dilation of the IR, which is mainly lined with a single-layered ciliated or non-ciliated squamous or cuboidal epithelium (Kon et al 2008), with considerably fewer pathological changes than the IR epithelium of CD-1 mice described by Long (2002). Additionally, a significant genetic linkage was obtained from the analysis of quantitative trait loci (QTL) between specific loci on chromosomes 4 or 14 and the development of ovarian cysts in MRL mice (Lee et al 2010). However, there is no evidence as to how the rete ovarii changes sequentially into an ovarian cyst in this mouse model (Kon et al 2008;Lee et al 2010).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast, the rete ovarian cysts of MRL mice showed dilation of the IR, which is mainly lined with a single-layered ciliated or non-ciliated squamous or cuboidal epithelium (Kon et al 2008), with considerably fewer pathological changes than the IR epithelium of CD-1 mice described by Long (2002). Additionally, a significant genetic linkage was obtained from the analysis of quantitative trait loci (QTL) between specific loci on chromosomes 4 or 14 and the development of ovarian cysts in MRL mice (Lee et al 2010). However, there is no evidence as to how the rete ovarii changes sequentially into an ovarian cyst in this mouse model (Kon et al 2008;Lee et al 2010).…”
Section: Introductionmentioning
confidence: 96%
“…Additionally, a significant genetic linkage was obtained from the analysis of quantitative trait loci (QTL) between specific loci on chromosomes 4 or 14 and the development of ovarian cysts in MRL mice (Lee et al 2010). However, there is no evidence as to how the rete ovarii changes sequentially into an ovarian cyst in this mouse model (Kon et al 2008;Lee et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the abundance of ovarian MCs around the surface epithelial region is a novel and unique phenotype of neonatal MRL mice. We previously reported that the reproductive organs of MRL mice have unique characteristics that are controlled by several factors derived from the genomic background of this strain [21,24,26,29,31]. Although the genomic background could be one of the factors controlling the appearance of ovarian MCs, the ancestral strains of MRL mice, namely AKR, C3H/He, and B6 mice, had lower MC densities than MRL mice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to autoimmune phenotypes, MRL mice show some unique phenotypes related to wound healing, such as accelerated ear punch closure and cardiomyocyte regeneration [1921]. In addition, we have reported that the reproductive organs of MRL mice have other unique characteristics: specifically, metaphase-specific apoptosis of meiotic spermatocytes [2224], heat shock resistance of spermatocytes found in experimental cryptorchidism [25,26], existence of testicular oocytes in newborn males [2729], and development of ovarian cysts originating from the rete ovarii [30,31]. These phenotypes are closely associated with the genetic background of MRL mice, and several susceptibility loci have been identified by genomic analysis [21,24,26,29,31].…”
Section: Introductionmentioning
confidence: 99%
“…But, other cysts are mostly nonfunctional. The precise causes of these nonfunctional ovarian cysts have not yet been fully elucidated [4,9]. Ovarian cysts in women are often associated with reproductive disorders like polycystic ovary syndrome (PCOS) [6].…”
mentioning
confidence: 99%